Screening of Detergents for Stabilization of Functional Membrane Proteins. (18th July 2018) - Lenoir, Guillaume; Dieudonné, Thibaud; Lamy, Anaïs; Lejeune, Maylis; Vazquez‐Ibar, José‐Luis; Montigny, Cédric
Abstract: Membrane protein studies usually require use of detergents to extract and isolate proteins from membranes and manipulate them in a soluble context for their functional or structural characterization. However, solubilization with detergent may interfere with MP stability and may directly affect MP function or structure. Moreover, detergent properties can be affected such as critical micellar concentration (CMC) can be affected by the experimental conditions. Consequently, the experimenter must pay attention to both the protein and the behavior of the detergent. This article provides a convenient protocol for estimating the CMC of detergents in given experimental conditions. Then, it presents two protocols aimed at monitoring the function of a membrane protein in the presence of detergent. Such experiments may help to test various detergents for their inactivating or stabilizing effects on long incubation times, ranging from few hours to some days. © 2018 by John Wiley & Sons, Inc.